Evaluation of lidocaine and tetracaine mixture in axillary brachial plexus block. - Berry JS; Heindel L (AANA Journal, 1999)
The mixture of 1% lidocaine and 0.2% tetracaine with 1:200,000 epinephrine, so-called 'supercaine,' has been used extensively for axillary brachial plexus blockade for several decades. Since the advent of bupivacaine, the supercaine mixture has fallen into relative disuse despite its record of effectiveness and safety. No studies have been done recently to evaluate quality of anesthesia, duration of postoperative analgesia, and degree of patient satisfaction with this mixture when used for axillary brachial plexus blockade. The assumptions were as follows: surgical anesthesia will be adequate, length of postoperative analgesia will be approximately 4 to 9 hours, and patients will be highly satisfied. The specific aim of the present study was to describe the anesthetic characteristics of supercaine. Patients between 18 and 65 years of age received a standard mixture of supercaine, totaling 450-500 mg of lidocaine and 90 to 100 mg of tetracaine. Epinephrine in a solution of 1:200,000 and an 8.4% solution of sodium bicarbonate were added, and the transarterial technique was used. Patients were contacted on postoperative day 1 to determine the duration of sensory and motor block; overall satisfaction with the block was rated. Data were analyzed with the Statistical Program for the Social Sciences (SPSS, Chicago, Ill) and Stata (Stata Corp., College Station, Tex) computer programs. The mean +/- SD findings were as follows: duration of sensory block, 465 +/- 204 minutes; duration of motor block, 473 +/= 214 minutes; patient satisfaction score, 9 +/- 1 on a 1 to 10 scale. Data are reported within a 95% confidence interval. Variables examined and compared were not statistically significant. We concluded that the duration of block supports findings reported in the literature, patients equate duration of sensory block with duration of motor block, differences in duration were probably due to levels of provider experience, and patients were extremely satisfied with the anesthetic.